Research on dynamic behavior of multistage gears-bearings and box coupling system. (January 2020) - Lu, Wenjia; Zhang, Yimin; Cheng, Hongchuan; Zhou, Yang; Lv, Hangyuan
Highlights: The coupling modeling method between multistage gear-rotor and box is proposed. Condensed stiffness matrix of box is extracted by static substructure method. Coupled box modeling reduces the vibration level of gearbox. It's helpful for lightweight design of the gearbox considering housing flexibility. Abstract: The coupling dynamic model of the multistage gears transmission subsystem and the box subsystem is established. The static substructure method is used to extract the dynamic model parameters of the box. Study of the dynamic behavior of the gearbox coupling system shows, the acceleration of the rotors are mainly excited by gear meshing frequency and its harmonic, meshing frequency of the high-speed gears has a more obvious excitation effect on the system, gear meshing excitation is the cause of the rotor's acceleration. It shows that the coupling model which is closer to the actual situation is helpful to the lightweight design of the system. The frequency amplitude of the low frequency region is significantly higher than the amplitude of the high frequency region for bearing force, which indicates that the external excitation caused by the cutting load is the main reason for the dynamic force of the system.